ANALISIS STRATEGI PENGEMBANGAN USAHA BANDREK LAMPUNG PADA UNIT USAHA THP HERBALIST - Asmarantaka, Aris; Sayekti, Wuryaningsih Dwi; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The aims of this research were to formulate the strategies for business development of Bandrek Lampung. This study was conducted at Hajimena Village of Natar District in South Lampung Regency by case study method. Alternative strategies formulated by the SWOT matrix. Strategic priorities of business development were formulated by FGD method. The Results showed that strategic priorities for business development were managing the bookkeeping of business; maintaining the continuity of production and quality control; and training the employee about everything of the business so that he can work without supervision, but the product quality remains excellent; taking advantage of developments in technology to improve business performance both in the production side, as well as promoting products; taking an interest in human resource development; focusing on business to approach the supplier; expanding product distribution into the strategic region with close monitoring; maintaining and improving the quality of the product; doing research to find a substitute in recipes and product innovation. Keywords: Bandrek Lampung, financial feasibility, FGD, strategy development, SWOT